Information System Success Model for the Evaluation of E-Government Applications in the Public Sector (Case Study: Whole App – Bandung Super App) - Paramita Paramita; Luthfi Ramadani; Basuki Rahmad (Eduvest - Journal of Universal Studies, 2026)
This study examines the effectiveness of an e-government application implemented by the Bandung City Government, namely the Kabeh (Bandung Super App), in supporting public service delivery. The background of this research is driven by the gap between the government’s objectives in providing digital public services and the actual user experience, which reflects low adoption, limited functionality, and user dissatisfaction. Therefore, this study aims to evaluate the success of the application using a modified DeLone and McLean Information Systems Success Model by incorporating Digital Literacy as an additional variable. This research employed a mixed methods approach, combining quantitative data through questionnaires and qualitative data through semi-structured interviews. The quantitative analysis measures relationships among variables such as System Quality, Information Quality, Service Quality, Digital Literacy, Intention to Use, User Satisfaction, and Net Benefit, while qualitative findings enrich the interpretation of user perceptions. The results indicate that Service Quality significantly influences Intention to Use, while Information Quality, Service Quality, Intention to Use, and Net Benefit significantly affect User Satisfaction. However, System Quality and Digital Literacy show no significant influence on both Intention to Use and User Satisfaction. Overall, the study concludes that the success of the application is primarily determined by service quality, information relevance, and perceived benefits, rather than technical aspects alone.